Study on hematological alterations induced by amphistomosis in buffaloes - Chauhan, Vandip. D. (Vet World, 2015)
AIM: The study was undertaken to compare the alterations in the hematological parameters in buffaloes suffering from Amphistomosis with normal buffaloes and to correlate it with the subclinical infection that is hard to diagnose. MATERIALS AND METHODS: Blood samples from 50 amphistomes infected as well as 50 non-infected buffaloes from slaughter houses were taken into vacutainer tubes containing ethylene diamine tetraacetic acid for estimation of various hematological parameters by Automatic Analyzer Hema-2062 manufactured by Analytical Technologies Ltd. RESULT: There was a significant reduction in the mean hemoglobin, total leukocyte count, total erythrocyte count and packed cell volume and significant increase in the neutrophils count and eosinophil count of infected buffaloes as compared to the non-infected buffaloes respectively. CONCLUSION: Amphistomosis is characterized by severe neutrophilia, eosinophilia, and anemia. Anemia of high intensity along with hepatic damage can lead to the death of the animal in severe cases. Alterations in the Hematological parameters can be used as an indicator to diagnose and check the severity of amphistomosis especially in young ones and in subclinical infection.